The Influence of Workload and Work Stress on Employee Performance with Job Satisfaction as an Intervening Variable: A Study at Tapin Utara Community Health Center, Tapin Regency, South Kalimantan - Ratna Susanti; Rahmi Widyanti; Basuki Basuki (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2026)
Employee performance is a central issue in primary healthcare organizations because the quality, speed, and consistency of public service depend heavily on the capacity of employees to complete clinical, administrative, and community-based tasks. This study examines the influence of workload and work stress on employee performance with job satisfaction as an intervening variable at Tapin Utara Community Health Center, Tapin Regency, South Kalimantan Province, Indonesia. The study employed a quantitative explanatory design using a structured questionnaire distributed to employees of the health center. The research model positioned workload and work stress as exogenous variables, job satisfaction as an intervening variable, and employee performance as the endogenous variable. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings show that workload and work stress have positive and significant effects on employee performance. Workload and work stress also have positive and significant effects on job satisfaction. Job satisfaction has the strongest positive and significant effect on employee performance and mediates the relationships between workload, work stress, and employee performance. The adjusted R-square value of 0.880 indicates that 88% of the variation in employee performance can be explained by workload, work stress, and job satisfaction. These findings imply that workload and work stress should not only be understood as risk factors but also as managerial conditions that, when kept proportional, meaningful, and manageable, may strengthen job satisfaction and improve performance in public healthcare institutions.